Effects of iba and media on the growth performance of three cultivars of grapes (Vitis Vinifera L.) - Zhou, Ruijin; Jia, Shanyi; Han, Feifei; Li , Kaiwei; Li, Guirong (Bangladesh Journal of Botany, 2023)
Annual branches of three grape cultivars, namely ‘Xia Hei’ grape, ‘Eastern Star’ grape and ‘Giant Rose’ grape were first treated with Indole-3-butyric acid (IBA) solution, then inserted in different media and then n their growth performances were studied. The growth performance of the three grape cultivars were: ‘Xia Hei’ > ‘Eastern Star’ > ‘Giant Rose’. Media (M4) was the most conducive to improve the survival per cent of gape rooted cuttings. This study provides a reference for choosing a suitable method to grow rooted cuttings taken from grape annual branches, which would furthermore improve the survival rate of young vines. Bangladesh J. Bot. 52(3): 763-774, 2023 (September)